Motor- and cognition-related safety of pimavanserin in patients with Parkinson's disease psychosis - Abler, Victor; Brain, Cecilia; Ballard, Clive; Berrio, Ana; Coate, Bruce; Espay, Alberto J. (Frontiers in Neurology, 2022)
Background Pimavanserin, a selective 5-HT2A inverse agonist/antagonist, is the only treatment approved by the US Food and Drug Administration for hallucinations and delusions associated with Parkinson's disease (PD) psychosis. Aim We aimed to evaluate motor- and cognition-related safety in pimavanserin-treated patients with PD psychosis. Methods This analysis included patients with PD psychosis treated with pimavanserin 34 mg from a pooled analysis of 3 randomized, double-blind, placebo-controlled, 6-week studies [NCT00477672 (study ACP-103-012), NCT00658567 (study ACP-103-014), and NCT01174004 (study ACP-103-020)] and a subgroup of patients with PD dementia with psychosis from HARMONY (NCT03325556), a randomized discontinuation study that included a 12-week open-label period followed by a randomized double-blind period of up to 26 weeks. Motor- and cognition-related safety were examined. Results The pooled analysis included 433 randomized patients (pimavanserin, 202; placebo, 231). Least squares mean (standard error [SE]) change from baseline to week 6 Unified Parkinson's Disease Rating Scale (UPDRS) II + III score was similar for pimavanserin [−2.4 (0.69)] and placebo [−2.3 (0.60)] (95% Confidence Interval [CI]:−1.9, 1.6). The change from baseline to week 6 for UPDRS II and UPDRS III scores was similar between groups. In the HARMONY open-label period, 49 patients with PD dementia with psychosis were treated with pimavanserin 34 mg, 36 of whom were randomized in the double-blind period (pimavanserin, 16; placebo, 20). In the open-label period, the mean (SE) change from baseline to week 12 (n = 39) Extra-Pyramidal Symptom Rating Scale (ESRS-A) score was −1.7 (0.74); in the double-blind period, the results were generally comparable between the pimavanserin and placebo arms. The change from baseline in Mini-Mental State Examination (MMSE) score was also comparable between pimavanserin- and placebo-treated patients in HARMONY [open-label (n = 37): mean (SE) change from baseline to week 12, 0.3 (0.66)]. Rates of motor- and cognition-related adverse events were similar between pimavanserin and placebo in both analyses. Conclusions Pimavanserin 34 mg was well tolerated and did not yield a negative impact on motor- or cognition-related function in patients with PD psychosis.